(untitled) (International Seven Journal of Health Research, 2024)
Lynch syndrome is a genetic condition that alters the production of DNA compatibility genes, which are responsible for monitoring the process of new cell formation in the body. Once compromised, this watchdog system fails and allows abnormal cells to develop, which sometimes initiates a process of malignization, resulting in the appearance of malignant tumours, especially in the colon and endometrial tissue. This text reports the clinical case of a young patient who was diagnosed with colorectal carcinoma and, after extensive outpatient and anatomopathological research, associated with a positive family history, was diagnosed with Lynch syndrome.